USAGE OF LOCAL ANAESTHESIA IN PAEDIATRIC DENTISTRY-A REVIEW - Vijaya Kumaran, Ghayathri; Jeevanandan, Ganesh; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this review is to summarize relevant usage of local anesthesia in pediatric dentistry. The objective of this review is to learn about the usage of local anesthesia associated with painless treatment, which reduces the anxiety level, and to ease the treatment in pediatric dentistry. Administering local anesthesia by injection is still the most common method used in dentistry. However, there is a constant search for ways to avoid the invasive and often painful nature of the injection and to find a more comfortable and pleasant means of producing local anesthesia before dental procedures in pediatric dentistry. Administration of local anesthesia with safety and fewer adverse effects when used in pediatric dentistry.